Acquisition Of Ownerless Land In The 150 KV Ketapang–Sukadana Transmission Line Project - Dadang Hardiana; Arina Novizas Shehbubakar (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The acquisition of ownerless land for national strategic infrastructure projects, particularly in the electricity sector, presents significant legal and administrative challenges. Ownerless land often becomes an obstacle to development due to unclear ownership status, resulting in delays in project implementation. This study aims to analyze the legal framework, regulatory implementation, and administrative constraints in the acquisition of such land. A normative legal research method is employed, utilizing statutory and case study approaches—specifically, the 150 kV Ketapang–Sukadana High Voltage Overhead Line (SUTT) project. Data were analyzed qualitatively through literature reviews, legal documents, and relevant reports. The findings indicate that the regulation concerning the use of ownerless land for public purposes and its financing is governed by Law No. 2 of 2012 on Land Acquisition for Development in the Public Interest and Supreme Court Regulation (PERMA) No. 3 of 2016. However, the implementation of these regulations remains problematic due to misinterpretations among stakeholders. Administrative constraints also arise from difficulties in obtaining complete documentation. These conditions have led to delays in national strategic projects and economic inefficiencies. Therefore, regulatory harmonization, data integration among relevant agencies, and capacity-building for involved parties are essential to enhance the efficiency of land acquisition processes.